Microorganisms in the female genital tract during pregnancy: tolerance versus pathogenesis - Ramos, Bruna de Andrade [UNESP]; Kanninen, Tomi T.; Sisti, Giovanni; Witkin, Steven S. (Wiley-Blackwell, 2015)
Microorganisms in the pregnant female genital tract are not always associated with pathology. The factors that influence the maternal response to microorganisms remain ill defined. We review the state of knowledge of microbe-host interactions in gestational tissues and highlight mechanisms that promote tolerance or pathogenesis. Tolerance to microorganisms is promoted during pregnancy by several mechanisms including upregulation of anti-inflammatory mediators, induction of endotoxin tolerance, and possibly by regulation of autophagy. Conversely, an altered vaginal microbiota or a pre-existing viral presence may result in induction of excessive inflammation and preterm labor. Although infections play a prevalent role in preterm birth, microbes are present in gestational tissues of women with healthy outcomes and may provide beneficial functions. The complex interactions between different microbial species and the maternal immune system during gestation remain incompletely elucidated.
Keywords: Autophagy; Immune tolerance; Microbial colonization; Microbial infection; Preterm birth